Perancangan Virtual Fitting Room Menggunakan Augmented Reality Pada Toko Online - Ariyanto (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2021)
In recent years, eMarketer data shows that Indonesia's e-commerce transactions reached 69.8 trillion in 2016. Even in 2018 it is predicted that it will continue to increase to IDR 144.1 trillion.The most influential satisfaction factor is the customer's perception of what is shown in the catalog.This study aims to visualize consumers using the products contained in the catalog. using Augmented Reality (AR) technology. The results show that the use of AR technology, which is built using TensorFlow, is able to recognize dimensional points on the human body so that clothing objects can be visualized on the consumer's body.